2019
DOI: 10.1177/1060028019891986
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Acute Kidney Injury in Neurologically Injured Patients Receiving Hypertonic Sodium Chloride: Does Chloride Load Matter?

Abstract: Background: Increasing evidence suggests that large-volume infusions of 0.9% sodium chloride (NaCl) for resuscitation are associated with hyperchloremic metabolic acidosis, renal vasoconstriction, and increased risk of acute kidney injury (AKI). Patients with neurological injury may require hypertonic NaCl for therapeutic hypernatremia, treatment of cerebral salt wasting, hyponatremia, or elevated intracranial pressure. Consequently, this increased exposure to chloride may result in an increased risk for devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Moreover, it was shown that chloride availability in the renal tubules can modulate renal vasoactivity; low chloride perfusion of diminishes tubular response to vasopressors (Quilley et al, 1993). In line with those observations, more recent clinical studies have suggested that high chloride load could be associated with an increased risk of acute kidney injury (Sigmon et al, 2019;Yunos et al, 2012). Therefore, it is conceivable that various biological impacts of serum or tubular concentrations of chloride represent a less well known territory with potential clinical implications.…”
Section: Chloride Homeostasismentioning
confidence: 86%
“…Moreover, it was shown that chloride availability in the renal tubules can modulate renal vasoactivity; low chloride perfusion of diminishes tubular response to vasopressors (Quilley et al, 1993). In line with those observations, more recent clinical studies have suggested that high chloride load could be associated with an increased risk of acute kidney injury (Sigmon et al, 2019;Yunos et al, 2012). Therefore, it is conceivable that various biological impacts of serum or tubular concentrations of chloride represent a less well known territory with potential clinical implications.…”
Section: Chloride Homeostasismentioning
confidence: 86%
“…We thank Gueret et al 1 for their comments on our recent article and acknowledge that we too understand that our retrospective study cannot answer all the issues regarding acute kidney injury (AKI) caused by hyperchloremia in the neurologically injured patient population. 1,2 The question posed regarding the risk of AKI in the neurologically injured population only stimulates more questions and research opportunities. We chose to use the acute kidney injury network (AKIN) criteria based on a previous study assessing AKI caused by hyperchloremia in a similar patient population.…”
Section: Letter To the Editormentioning
confidence: 99%
“…We thank Gueret et al 1 for their comments on our recent article and acknowledge that we too understand that our retrospective study cannot answer all the issues regarding acute kidney injury (AKI) caused by hyperchloremia in the neurologically injured patient population. 1,2…”
mentioning
confidence: 99%
“…
We are interested in the article written by Sigmon et al 1 The authors concluded that hypertonic sodium therapy with high chloride load, for neurologically injured patients, increases risk of developing hyperchloremia and acute kidney injury (AKI). However, we have questions.The authors defined AKI as change in serum creatinine of 0.3 mg/dL or an increase to 1.5 times baseline.
…”
mentioning
confidence: 99%
“…5 Finally, this study gives us some answers on the relationship between chloride load and AKI in neurologically injured patients. 1 However, a few elements are missing to arrive at a conclusion, particularly the amount of hypertonic saline received by patients. It is like the chicken and the egg question: Is AKI a result of the amount of hypertonic saline solution or patients' injury severity?…”
mentioning
confidence: 99%